The sensing mechanism and detection of low concentration acetone using chitosan-based sensors - Tulus Ikhsan, Nasution; Irwana, Nainggolan, Dr.; Sabar Derita, Hutagalung, Dr.; Khairel Rafezi, Ahmad, Dr.; Zainal Arifin, Ahmad (Elsevier B. V., 2013)
Link to publisher's homepage at http://www.elsevier.com/